2012
DOI: 10.1002/wsb.239
|View full text |Cite
|
Sign up to set email alerts
|

Population demographics of translocated northern bobwhites on fragmented habitat

Abstract: Habitat fragmentation is considered a contributing factor to declining populations of northern bobwhite (Colinus virginianus). Some population strongholds exist within large expanses of habitat; however, many regions of the species' range have become fragmented and populations therein have become nearly extirpated. Our objectives were to determine whether combined habitat management and bobwhite translocation could restore bobwhite populations in habitat patches within a fragmented landscape. We translocated 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 19 publications
(42 reference statements)
7
25
0
Order By: Relevance
“…We also calculated potential and realized estimates of percentage of nesting females and nesting rate (no. nests/F; Hernández et al , Scott et al ). We calculated potential estimates using only translocated radio‐marked females that survived the entire nesting season (1 May−31 Aug) and therefore the estimates captured the entire nesting history of females.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also calculated potential and realized estimates of percentage of nesting females and nesting rate (no. nests/F; Hernández et al , Scott et al ). We calculated potential estimates using only translocated radio‐marked females that survived the entire nesting season (1 May−31 Aug) and therefore the estimates captured the entire nesting history of females.…”
Section: Methodsmentioning
confidence: 99%
“…The translocation of wild bobwhites has received limited research attention, and the few studies that have been conducted have yielded contrasting results (Liu et al , Terhune et al , Scott et al ). For example, Scott et al () reported lower survival and productivity of translocated bobwhites in central Texas compared to resident bobwhites. Conversely, other studies have reported similar survival and productivity between translocated and resident bobwhites (Liu et al ; Terhune et al , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Translocation has been used to reintroduce or restock northern bobwhite (Colinus virginianus) populations with varied results (Kabat and Thompson 1963;Jones 1999;Perez et al 2002;Terhune et al 2006aTerhune et al , 2006bTerhune et al , 2010Scott et al 2013). These studies compared vital rates of translocated to resident bobwhites, focusing on survival and reproductive effort or success of translocated individuals; however, survival of the offspring of translocated individuals has not been studied (Jones 1999;Perez et al 2002;Terhune et al 2006aTerhune et al , 2006bTerhune et al , 2010Scott et al 2013). Offspring survival is an important factor influencing population growth rates (Wisdom andMills 1997, Sandercock et al 2005).…”
mentioning
confidence: 99%
“…More comprehensive recent studies involved birds translocated over shorter distances and demonstrate much greater survival rates. Terhune et al (, 2010), Liu et al (), and Jones () reported no significant difference in survival rates between translocated and resident bobwhites, whereas Scott et al () reported significantly (30–40%) lower survival rates for translocated birds compared with resident birds. Still, translocated birds, though fewer in number, have a greater survival rate than captive‐reared birds.…”
Section: Survival Ratementioning
confidence: 98%